Psychometric properties of the smartphone addiction proneness scale in a sample of Malaysian adolescents - Sii Jiing Chan; Kee Jiar Yeo; Lina Handayani (Intelektual Pustaka Media Utama, 2022)
The aim of this study was to examine the psychometric properties of the 15-item smartphone addiction proneness scale (SAPS) among a sample of Malaysian adolescents. The gathered data were subjected to exploratory and confirmatory factor analysis. There were 922 secondary school students involved in this study. The exploratory factor analysis extracted a three-factor solution for SAPS. These factors were named disturbance of adaptive functions, withdrawal and tolerance. Results from confirmatory factor analysis also indicated that the three-factor structure fits well with the data. The internal consistency of the scale was found to be good. The positive and moderately strong correlation between SAPS and three widely adopted criterion variables (depression, loneliness and boredom proneness) supported the concurrent validity of SAPS. The results of this study showed that the SAPS is a reliable and valid instrument for identifying problematic smartphone use among Malaysian adolescents.